Low-level viral loads and virological failure in the integrase strand transfer era. (6th March 2023) - Cuzin, Lise; Flandre, Philippe; Allavena, Clotilde; Palich, Romain; Duvivier, Claudine; Becker, Agathe; Laroche, Hélène; Pugliese, Pascal; Cabie, André; ,
Abstract: Objectives: To analyse the occurrence of virological failure (VF) in patients starting ART with an integrase strand transfer inhibitor (INSTI)-based regimen in recent years, in relation with previous episodes of low-level viral load (LLVL). Patients and methods: Patients starting a first ART between 1 January 2015 and 31 December 2020 based on two NRTIs and one INSTI were included if after virological control (two measures of VL < 50 copies/mL) they had a minimum of two additional VL measurements. Cox models adjusted for sex, age, acquisition group, hepatitis B or C coinfection, place of birth, year of ART initiation, CD4+ T cells and VL at ART initiation, duration of known HIV infection and of ART regimen were used to assess the association between the time to VF and the occurrence of LLVL. ART regimen was evaluated as time-varying covariate. Results: LLVL was described in 13.7% and VF in 11% of the 3302 patients. LLVL was associated with VF [adjusted HR (aHR) 1.76, 95% CI 1.28–2.41], as well as age (aHR 0.97/year, 95% CI 0.96–0.98), CD4+ T cell count at ART initiation (aHR 0.93, 95% CI 0.87–0.98), heterosexual transmission (aHR 1.76, 95% CI 1.30–2.37) and being born abroad (aHR 1.50, 95% CI 1.17–1.93). Conclusions: LLVL was related to VF. Even in the absence of subsequent failure, LLV episodes have a cost. Thus any VL value above 50 copies/mL should lead to enhanced adherence counselling.